Konsep Pendidikan Karakter Prespektif Kitab Adab Al-'Alim Wa Al-Mu'ta'allim - M. Munir (Asosiasi Dosen Tarbiyah STAI Darussalam Nganjuk, 2021)
Character Education Management is actually the process of cultivating character values to students or students, and in the Book of Ᾱdᾱb Al-Ᾱlim Wa Al Muta'allim whose notabennya classic book has established a unique managerial activity in character education to students, both in the scope of formal, non-formal, and informal education. Character Education Management in the book of Ᾱdᾱb Al 'Ᾱlim Wa Al Mutaallim includes Planning, in the form of heartbreak and determination of intentions for teachers and students, Organizing in the form of material grouping, class division based on age and ability, Actuating in the form of motivation and encouragement through verses of the Qur'an and hadith, and Controlling embodied explanations of ethical forms and morals of teachers and students towards themselves. In the book of Ᾱdᾱb Al 'Ᾱlim Wa Al Mutaallim contains management functions, namely Planning, Organizing, Actuating, and Controlling (POAC), with the focus of educational institutions are formal educational institutions